Gender differences in the associations among adolescent problem behaviors: a secondary data analysis of the 2023 Korea Youth Risk Behavior Survey - Jaeyoung Lee; So Yeon Park (Child Health Nursing Research, 2025)
Purpose This study aimed to investigate the association among various adolescent problem behaviors in South Korea, focusing on gender differences. Methods This secondary analysis was conducted using cross-sectional data from the 19th Korea Youth Risk Behavior Survey, conducted in 2023 which included 52,880 middle and high school students in South Korea. They completed an anonymous self-administered survey regarding problem behaviors (drinking alcohol, smoking, drugs use, and sexual experiences). Data were analyzed using complex-samples chi-square and multiple logistic regression models. Results Among the 52,880 adolescents, the prevalence rates of alcohol use, smoking, drug use, and sexual experiences were 32.6%, 8.6%, 1.7%, and 6.5%, respectively. Gender differences were observed in alcohol use complex-samples multiple logistic regression models. However, no significant gender difference was found in drug use (p=.250). Four problem behaviors were significantly associated with one other when analyzed as independent variables (odds ratio [OR], 1.33–10.85). The strongest associations were found between alcohol use and smoking (OR, 10.49–10.85), and between smoking and sexual experiences (OR, 4.91–4.96). Conclusion This study found significant gender differences in adolescent problem behaviors, with male adolescents exhibiting higher rates of alcohol use, smoking, and sexual experience. Strong associations were observed between alcohol use and smoking, as well as between smoking and sexual experience. These findings suggest the need for integrated intervention strategies that target multiple co-occurring problem behaviors.